Autobiography in Anthropology: A Thirty Year Retrospective. Issue 1 (1st March 2022) - Laviolette, Patrick; Bošković, Aleksandar
Abstract : The year 2022 marks the 30th anniversary of the release of Helen Callaway and Judith Okely's edited anthology Anthropology and Autobiography. During that generational span, which roughly mirrors the life history of this journal, the book has had far-reaching influences, anchoring a legacy that few such conference collections can imagine for themselves. Indeed, the volume has become a classic reference work for scholars in all walks of the social sciences and humanities when it comes to considering a range of interrelated themes: the reflexive turn; personal encounters in the field; the literary influence of the biographical on ethnography; anthropology's ancestries/histories (Lohmann 2008; Pina-Cabral and Bowman 2020); and so on. Another aspect of this endeavour is looking at 'anthropology at home' (Jackson 1987), with all the implications that this brings for research (Peirano 1998), including the notion of 'auto-anthropology' (Rapport 2014: 24–35).